Developing competency in video-assisted thoracic surgery (VATS) lobectomy - Konge, Lars; Petersen, René Horsleben; Ringsted, Charlotte (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
The first thoracoscopy was performed by Jacobeus in 1910 (1) and today the technique has evolved to a point where the majority of thoracic procedures can be performed using a minimally invasive technique.